Implementation of Pancasila Values in the New Order Era and Post-Reformation - Rahmat Salam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Pancasila is the basis of our country and the nation's view of life, which is extracted from the noble values of the nation's culture. However, along with the development of time, the practice and implementation of the Pancasila practice are always adjusted to the regime's will in power. In the Old Order era, Pancasila was used as an ideological tool; during the New Order, Pancasila was carried out purely and consistently but followed the regime's will in power at that time. In the Reformation Age, the implementation of Pancasila, which was expected to be following the original, even began to be abandoned because the people were more faced with a free lifestyle with liberal understanding. This article will try to highlight the position of Pancasila during the New Order regime when President Suharto was in power and compare it with the work of Pancasila Post-reformation starting from the fall of the New Order until now and looking at the challenges that will be faced in the future.